Targeting Mitochondrial Dysfunction in Chronic Heart Failure: Current Evidence and Potential Approaches - Aimo, Alberto; Borrelli, Chiara; Vergaro, Giuseppe; F. Piepoli, Massimo; R. De Caterina, Alberto; Mirizzi, Gianluca; Valleggi, Alessandro; Raglianti, Valentina; Passino, Claudio; Emdin, Michele; Giannoni, Alberto (Current Pharmaceutical Design, 2016)
Background: Mitochondria are cellular organelles responsible for energy production, calcium handling, controlled synthesis of reactive oxygen species (ROS), and regulation of apoptosis. All these functions are crucial for cardiac homeostasis, and may be impaired in chronic heart failure (CHF). Therefore, mitochondrial dysfunction might represent a crucial element in the onset and progression of CHF and, as such, a promising therapeutic target. Methods: Original articles and review on the treatment of mitochondrial dysfunction in CHF were searched on Medline and Scopus. Results: The present review summarizes the current knowledge about mitochondrial modulation as a therapeutic strategy for CHF, and proposes some perspectives for future studies. Mitochondrial dysfunction can be ascribed to neuro-humoral activation and cardiac remodeling associated with CHF. Conceptually, the correction of mitochondrial dysfunction could provide an additive benefit to optimal CHF treatment. Increasing glucose metabolism and reducing oxidative stress within mitochondria are the two most promising approaches, even though further studies are required before implementing new treatments in the setting of CHF. On the other hand, inhibition of apoptosis, and normalization of calcium and mitochondrial dynamics have been assessed almost exclusively in ex vivo models, and mostly in settings other than CHF. Conclusion: Mitochondrial modulation in CHF is an intriguing example of translational research and a potentially rewarding field.
Keywords: apoptosis